FIGURE 8 in Taxonomy of high-latitude Goniasteridae (Subantarctic & Antarctic): one new genus, and three new species with an overview and key to taxa - Mah, Christopher L. (Zenodo, 2011)
FIGURE 8. Cladaster analogus "big form" USNM 1091176. A. Abactinal surface. B. Close-up of abactinal plates. C. Actinal surface. D. Lateral view of superomarginal and inferomarginal plates. Published as part of Mah, Christopher L., 2011, Taxonomy of high-latitude Goniasteridae (Subantarctic & Antarctic): one new genus, and three new species with an overview and key to taxa, pp. 1-48 in Zootaxa 2759 on page 21, DOI: 10.5281/zenodo.276783